Injection System Cultiving Machine for Plant Soybean in Panduman Village, Jelbuk District, Jember District - Robertoes Koekoeh Koentjoro Wibowo; Widjonarko Widjonarko; Dwi Djumhariyanto (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
This low soybean production is caused by various factors, including farming technology that is still not good, the readiness and skills of soybean farmers are still lacking, The current conventional/traditional system used by farmers to grow soybeans is to make holes with a small hole or wood. After that put 2-3 soybean seeds in each hole and then cover it with soil, this kind of activity takes a long time, causing discomfort for farmers or farm workers. The target of this activity is farmers by encouraging them planting soybeans in Panduman Village which is still possible from a geographical point of view and directing profit-oriented farming in an effective planting time process. In the planting activity, the design prototype planted soybeans in 2 planting rows with a working capacity of ≤ 18 hours/ha with a seed output of 2-3 seeds/planting hole and a planting depth of 3-5 cm and regular spacing of 40 cm and the seeds were covered with soil cover. The design of the development of this planting machine is considered quite good in planting soybeans.